(untitled) (Environment & Health, 2022)
The aim of study: determination of the genetic factor’s involvement (MTHFR:C677T polymorphism), which affects the activity of the main enzyme of the folate cycle, methylenetetrahydrofolate reductase, and environmental exposure, including the radiation factor, in the occurrence of hyperhomocysteinemia in children which living near the Chornobyl Exclusion Zone (ChEZ). Research methods. Immunochemical, mathematical and statistical. Results. Within the framework of international projects, the levels of homocysteine (Hcy) and allelic variants of the genetic polymorphism MTHFR:C677T were determined in 624 children aged 13-17 years old from Ivankivskyi and Poliskyi districts of the Kyiv region. It has been established that an increase in the level of Hcy in the blood and an increase in the number of cases of hyperhomocysteinemia in the examined groups of children are associated with forest fires in the ChEZ in 2015 and 2020. Under conditions of pronounced exposure to radioactive agents and combustion products of forest trees, the proportion of cases of hyperhomocysteinemia in groups of children with and without the T allele of the MTHFR:677 polymorphism in the genome did not have statistical differences. An indicator of ecological trouble in the ChEZ and adjacent areas is an increase, above the physiological level, in the concentration of Hcy in the blood of adolescent children with the absence of the T allele of the MTHFR:677 polymorphism in the genome. Conclusion. In areas affected by the accident at the Chornobyl nuclear power plant, it is necessary to constantly conduct regular monitoring studies of the health of children, using tests for the content of Hcy in the blood and the state of the folate cycle genes.